A Nanobody Recognizes a Unique Conserved Epitope and Potently Neutralizes Sars-Cov-2 Omicron Variants - Chana-Cuevas, P (Elsevier Inc., 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) Omicron variant sub-lineages spread rapidly worldwide, mostly due to their immune-evasive properties. This has put a significant part of the population at risk for severe disease and underscores the need for effective anti-SARS-CoV-2 agents against emergent strains in vulnerable patients. Camelid nanobodies are attractive therapeutic candidates due to their high stability, ease of large-scale production, and potential for delivery via inhalation. Here, we characterize the receptor binding domain (RBD)-specific nanobody W25 and show superior neutralization activity toward Omicron sub-lineages in comparison to all other SARS-CoV2 variants. Structure analysis of W25 in complex with the SARS-CoV2 spike glycoprotein shows that W25 engages an RBD epitope not covered by any of the antibodies previously approved for emergency use. In vivo evaluation of W25 prophylactic and therapeutic treatments across multiple SARS-CoV-2 variant infection models, together with W25 biodistribution analysis in mice, demonstrates favorable pre-clinical properties. Together, these data endorse W25 for further clinical development. © 2023